A Comparability Study on Driver Fatigue Using C#, C++ and Python - Raman, K.J.; Azman, A.; Ibrahim, S.Z.; Yogarayan, S.; Abdullah, M.F.A.; Abdul Razak, S.F.; Muhamad Amin, A.H.; Sonai Muthu, K. (International Journal of Human and Technology Interaction (IJHaTI), 2018)
Accidents on road are very common these days. Most of them are caused by driver fatigueness. Some common causes and symptoms have been identified. One of the main solution to detect driver fatigue is by analyzing the facial features of the drivers. This paper discusses about the facial features that can be used to detect driver fatigue. Further examples on existing vehicle safety technology is also discussed. Primarily, this work emphasizes on the study of three different programming languages and its compatibility which works best to be integrated with the proposed hardware. Based on the study, the result is discussed and the suitable programming language is suggested.